Magic Shotgun Nature with Scattergun Approach of Curcumin Repurposing in Obsessive-compulsive Disorder: A Novel Metaphysician of Drug Discovery - Mishra, Rahul K.; Mishra, Ashutosh; Gupta, Amresh (CNS & Neurological Disorders - Drug Targets, 2021)
Background: Obsessive-Compulsive Disorder (OCD) is an intricate, debilitating neuropsychiatric disorder. Exclusively, Selective Serotonin Reuptake Inhibitors (SSRIs) are effective agents used for the treatment of OCD. However, SSRIs are not a magic pill-they do not respond adequately to everybody. In this consideration, a single drug target (magic bullet) is only a slightly superior option for all patients with a lot of pathognomonic signs. Objective: The principal aim of the current study was to check the potential contribution of repurposing of magic shotgun nature of curcumin (rhizomes of Curcuma longa) with scattergun approach- proceeding a pioneer ‘fine-tune’ for obsessive-compulsive disorder. Method: Swiss albino mice (male 20 to 25 gram) were grouped into different groups (n = 6) used for the MBB (marble-burying behaviour) and MA (motor activity) test as a model for evaluation of anti-compulsive activity (Anti-OCD). Ethanolic extract of Curcuma longa (EECL-10, 15, 25, 40 mg/kg), or SSRI (fluoxetine 5, 10, 15 mg/kg) followed by pre-treated with either sub effective dose of fluoxetine attenuated MBB without effected the MA, or neurotoxin p-chlorophenyl alanine induced compulsive behavior and specific 5-HT receptors agonists/ antagonist, intraperitoneally revealed neuromodulation. Results: EECL (40 mg/kg) significantly attenuated the MBB. Although, during treatments, none of the above had any critical impact on MA. p < 0.05 was considered significant in every case. Conclusion: Multiple drug-target interactions with multifarious biogenic receptors, supervene unexpected side effects followed by the repurposing of wanted effects (scattergun effect) were evoked by curcumin treatment. Finally, the study shows that EECL (curcumin) has anti-compulsive activity, which is mediated by neuromodulation with 5-HT receptors.
Keywords: scattergun